A Hypoxia-Related miRNA-mRNA Signature for Predicting the Response and Prognosis of Transcatheter Arterial Chemoembolization in Hepatocellular Carcinoma - Zong S; Huang G; Pan B; Zhao S; Ling C; Cheng B (Journal of Hepatocellular Carcinoma, 2024)
Shaoqi Zong,1,2,* Guokai Huang,1,3,* Bo Pan,1,* Shasha Zhao,4 Changquan Ling,1,3 Binbin Cheng1,3 1Oncology Department of Traditional Chinese Medicine, The First Affiliated Hospital of Naval Medical University, Shanghai, 200043, People’s Republic of China; 2Department of Oncology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People’s Republic of China; 3Faculty of Traditional Chinese Medicine, Naval Medical University, Shanghai, 200043, People’s Republic of China; 4Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200071, People’s Republic of China*These authors contributed equally to this workCorrespondence: Binbin Cheng, Oncology Department of Traditional Chinese Medicine, The First Affiliated Hospital of Naval Medical University, 168 Changhai Road, Shanghai, 200043, People’s Republic of China, Email cbb8202@smmu.edu.cn Changquan Ling, Faculty of Traditional Chinese Medicine, Naval Medical University, 800 Xiangyin Road, Shanghai, 200043, People’s Republic of China, Email changquanling@smmu.edu.cnPurpose: Transcatheter arterial chemoembolization (TACE) is commonly used in the treatment of hepatocellular carcinoma (HCC). However, not all patients respond to this treatment. TACE typically leads to hypoxia in the tumor microenvironment. Therefore, we aimed to construct a prognostic model based on hypoxia-related differentially expressed microRNA (miRNAs) in hepatocellular carcinoma (HCC) and to investigate the potential target mRNAs for predicting TACE response.Methods: The hypoxia-related miRNAs (HRMs) were identified in liver cancer cells, then global test was performed to further select the miRNAs which were associated with recurrence and vascular invasion. A prognostic model was constructed based on multivariate Cox regression analysis; qRT-PCR analysis was used to validate the differentially expressed miRNAs in HCC cell lines under hypoxic condition. We further identified the putative target genes of the miRNAs and investigate the relationship between the target genes and TACE response, immune cells infiltration.Results: We established a HRMs prognostic model for HCC patients, containing two miRNAs (miR-638, miR-501-5p), the patients with high-HRMs score showed worse survival in discovery and validation cohort; qRT-PCR analysis confirmed that these two miRNAs are up-regulated in hepatoma cells under hypoxic condition. Furthermore, four putative target genes of these two miRNAs were identified (ADH1B, CTH, FTCD, RCL1), which were significantly associated with TACE response, immune score, immunosuppressive immune cells infiltration, PDCD1 and CTLA4.Conclusion: The HCC-HRMs signature may be utilized as a promising prognostic factor and may have implications for guiding TACE and immune therapy.Keywords: hypoxia, miRNA, signature, hepatocellular carcinoma, prognosis